Effect of Melaleuca alternifolia mixed with tissue conditioners in varying doses on colonization and inhibition of Candida albicans: An in vitro study - Siva Kumar Vankadara; Rajendra Basavaraj Hallikerimath; Viraj Patil; Kishore Bhat; Mallikarjun Hanumantappa Doddamani (Wolters Kluwer Medknow Publications, 2017)
Aims and Objectives: The study was conducted to evaluate the Colonization & Inhibition of Candida albicans in selected commercially available denture lining materials material by mixing them with varying concentrations and doses of tea tree oil. Materials and Methods: Five test discs of 10mm diameter and 1.5mm thickness were prepared using commercially available soft denture lining materials (Viscogel and GC-soft). Tea tree oil of varying concentrations (10%, 20%, 30%, and 40%) and doses (0.5 ml, 1.0 ml, 1.5 ml, 2.0 ml) were added during manipulation. Test discs kept in sterile artificial saliva were inoculated with Candida albicans (ATCC-2091 strain) and incubated for 6 weeks. These discs were fixed, dehydrated air dried and stained using 0.03% acridine orange stain and observed under Fluorescent microscope to count the colonies on the surface of each disc to evaluate the colonization. To evaluate inhibition, test discs were placed on the top of Sabouraud's dextrose agar inoculated with Candida albicans (ATCC-2091 strain). After incubation at 370C for 48 hours, the zone of Inhibition formed around the samples was measured. Results: The GC soft liner had higher mean colonization and lesser zone of inhibition of C.albicans when compared to Visco-gel soft liner (P < 0.001) and highest zone of inhibition observed with 2 ml volume and 40% vol/vol concentration of melaleuca alternifolia (P < 0.05). Interpretation and Conclusion: By the addition of Tea Tree oil, Viscogel had good acquired good antifungal properties than GC-soft lining materials.